The Role of PDE11A4 in Social Isolation-Induced Changes in Intracellular Signaling and Neuroinflammation - Pilarzyk, Katy; Farmer, Reagan; Porcher, Latarsha; Kelly, Michy P. (Frontiers in Pharmacology, 2021)
Phosphodiesterase 11A (PDE11A), an enzyme that degrades cyclic nucleotides (cAMP and cGMP), is the only PDE whose mRNA expression in brain is restricted to the hippocampal formation. Previously, we showed that chronic social isolation changes subsequent social behaviors in adult mice by reducing expression of PDE11A4 in the membrane fraction of the ventral hippocampus (VHIPP). Here we seek extend these findings by determining 1) if isolation-induced decreases in PDE11A4 require chronic social isolation or if they occur acutely and are sustained long-term, 2) if isolation-induced decreases occur uniquely in adults (i.e., not adolescents), and 3) how the loss of PDE11 signaling may increase neuroinflammation. Both acute and chronic social isolation decrease PDE11A4 expression in adult but not adolescent mice. This decrease in PDE11A4 is specific to the membrane compartment of the VHIPP, as it occurs neither in the soluble nor nuclear fractions of the VHIPP nor in any compartment of the dorsal HIPP. The effect of social isolation on membrane PDE11A4 is also selective in that PDE2A and PDE10A expression remain unchanged. Isolation-induced decreases in PDE11A4 expression appear to be functional as social isolation elicited changes in PDE11A-relevant signal transduction cascades (i.e., decreased pCamKIIα and pS6-235/236) and behavior (i.e., increased remote long-term memory for social odor recognition). Interestingly, we found that isolation-induced decreases in membrane PDE11A4 correlated with increased expression of interleukin-6 (IL-6) in the soluble fraction, suggesting pro-inflammatory signaling for this cytokine. This effect on IL-6 is consistent with the fact that PDE11A deletion increased microglia activation, although it left astrocytes unchanged. Together, these data suggest that isolation-induced decreases in PDE11A4 may alter subsequent social behavior via increased neuroinflammatory processes in adult mice.